Nilai Moral Dalam Tradisi Berbalas Pantun Pada Perkawinan Di Kecamatan Tanjung Pura Kabupaten Langkat - Trisfayani Trisfayani; Della Mailani; Reza Pahlevi Ginting (Jurnal Ilmiah Kanderang Tingang, 2024)
This research aims to describe the types of moral values ​​and forms of conveying moral values ​​in the tradition of reciprocating rhymes at weddings in Tanjung Pura District, Langkat Regency. The research method used is descriptive qualitative. Data collection techniques in this research are documentation, recording, listening and taking notes. The data used in this research are words sung by poets or telangkai during wedding parties in Tanjung Pura District, Langkat Regency. The data source for this research is poets or telangkai who sing pantun. Based on the research results, 27 types of moral values ​​were found. These types of moral values ​​are divided into three, namely (1) the relationship between humans and themselves with 3 data, (2) the relationship between humans and other humans with 21 data, and (3) the relationship between humans and God with 3 data. The form of conveying moral values ​​is divided into two, namely (1) the direct form of delivery with 17 data, and (2) the indirect form of delivery with 10 data.Keywords: Moral Values, Tradition of Reciprocating Rhymes, Marriage